2015
DOI: 10.1016/j.solener.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical-thermal analysis of III–V triple-junction solar cells under variable spectra and ambient temperatures

Abstract: The influence of the incident spectral irradiance on the electrical and thermal behaviour of triple-junction solar cells has been investigated. A spectral dependent electrical model has been developed to calculate the electric characteristics and quantify the heat power of a multijunction solar cell. A three-dimensional finite element analysis is also used to predict the solar cell's operating temperature and cooling requirements for a range of ambient temperatures. The combination of these models improves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…where h is the convective heat transfer coefficient (W / m 2 K ), T s is the exposed surface temperature ( • C), T ∞ is the ambient temperature and is assumed to be 25 • C, ε is the emissivity of the surfaces that are subjected to radiation, and σ is the Stefan-Boltzmann constant. For radiation heat transfer, the sky temperature was assumed to be equal to the ambient temperature as introduced in Equation 22for simplification, as suggested in the literature [3,17]. For the MJ solar cell domain, the law of energy conversion for a steady-state with a heat source term…”
Section: Grid Independence Studymentioning
confidence: 99%
“…where h is the convective heat transfer coefficient (W / m 2 K ), T s is the exposed surface temperature ( • C), T ∞ is the ambient temperature and is assumed to be 25 • C, ε is the emissivity of the surfaces that are subjected to radiation, and σ is the Stefan-Boltzmann constant. For radiation heat transfer, the sky temperature was assumed to be equal to the ambient temperature as introduced in Equation 22for simplification, as suggested in the literature [3,17]. For the MJ solar cell domain, the law of energy conversion for a steady-state with a heat source term…”
Section: Grid Independence Studymentioning
confidence: 99%
“…The annual average inputs (after filtering) for Las Vegas and Tucson are given in Table 1. An electrical model (EM) using the single-diode circuit was developed [13] to handle bulk spectra and to simulate the electrical performance of the Spectrolab C1MJ concentrator cell assembly (CCA). EQE data were adopted from Kinsey and Edmondson [14] and the procedure described by Steiner et al [15] was used to calculate the EQE at any operating temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In order to simplify the integrated modelling procedure and to also reduce the computational time, multiple regression analysis was then used for the T cell prediction [3]. The equations, boundary conditions and input data for the EM and FETM models are presented by Theristis and O'Donovan [13,16]. The spectral performance is evaluated using the spectral factor (SF) [17] and the spectral matching ratio between the top and middle subcells (SMR) [18] as criteria.…”
Section: Methodsmentioning
confidence: 99%
“…For single cell geometries, passive cooling is typically capable of handling the heat flux due to the large area available for heatsinking [8]. Theristis et al [9] reported that a single cell configuration with a solar cell area of 1 cm 2 can be cooled passively for concentration ratios of up to 500× with a heat sink. For linear concentrators and densely packed cells under high concentrations over 150 Suns, an active cooling system is necessary, while passive cooling is usually insufficient to handle this situation since less area is available for heatsinking.…”
Section: Introductionmentioning
confidence: 99%